Subterranean Worlds: A Critical Anthology - Roslynn Haynes (2006)
Peter Fitting, Director of the Cinema Studies Program at the University of Toronto regards this book as "somewhere between a hobby and an obsession," drawing, as it does, on his interest in literary utopias and science fiction. In it he traces the theme of a subterranean world through some fifteen novels, from the anonymous Relation d'un voyage du Pole Arctique au Pole Antarctique (1721) to Edgar Rice Burroughs's At the Earth's Core (1914). Each chapter offers a brief introduction, including a synopsis of the narrative, followed by extracts from the novel, chosen to indicate how the adventurer-narrator arrived there, a description of the subterranean world, how it is illuminated and, where appropriate, the society that exists there.